Photographing the Aspiration of the Hindu-Islam as Interfaith Dialogue Policy: a Case in Klinting Village, Somagede, Banyumas, Indonesia - Ubaidillah Ubaidillah (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Managing plural and multicultural diversity of citizens is an obligation mandated by the constitution and the third precept of Pancasila. One of the efforts to care for diversity within the framework of Indonesian unity is through interfaith dialogue which is packaged in fostering religious harmony. With the issuance of Village law 16 of 2014 has provided space for aspirations to manage the diversity of citizens through the deleberative democracy process in the village budget policy mechanism in Village Development Conference. This research has found grassroots aspirations that are included in the Village Fund policy in Klinting Village, Banyumas district. Although it is not the main aspiration in the village budget policy priorities, it is at least a quality aspiration that is included in the village fund policy. The issue of religion in the form of interreligious dialogue between Hindu-Islamic religions is still a common thread in the realities of policy and the aspirations of people's lives, that is the aspiration demonstration that can be achieved from this research.